Michelson Interferometer Based Displacement Measurement Using Video Processing - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2015)
In this study, investigation of video processing method which is a new technique for precision displacement measurement is presented. The video processing method was integrated with an interferometric system and the thermal expansion results and linear thermal expansion coefficients of a heated sample metals were compared with theoretical results. Michelson interferometer setup was used in our study due to its advantages in precision displacement information of a visual output, called interferograms. In the experimental studies, signals of interferograms containing displacement information were obtained from the measurement system. The amount of displacement in the sample metals under the temperature variation due to thermal expansion was measured with the analysis program, written in Matlab/Simulink environment, with a micrometer precision. The measured displacement amounts were compared with the results of theoretical calculations. According to the theoretical values, the relative error of the values measured with video processing based method, was found found to be 0.3%
Keywords: LASER-INTERFEROMETER